2008
DOI: 10.1074/jbc.m709829200
|View full text |Cite
|
Sign up to set email alerts
|

RACK1, a New ADAM12 Interacting Protein

Abstract: ADAM12 belongs to a disintegrin-like and metalloproteinase-containing protein family that possesses multidomain structures composed of a pro-domain, a metalloprotease, disintegrin-like, cysteine-rich, epidermal growth factor-like, and transmembrane domains, and a cytoplasmic tail. Overexpression of several ADAMs has been reported in human cancer, and we recently described the involvement of ADAM12 in liver injury (Le Pabic, H., Bonnier, D., Wewer, U. M., Coutand, A., Musso, O., Baffet, G., Clement, B., and The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
22
0

Year Published

2010
2010
2015
2015

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(27 citation statements)
references
References 63 publications
5
22
0
Order By: Relevance
“…Accordingly, we observed a severe reduction in the transport of synaptotagmin-labeled (cycling) SV to distal parts of neuronal processes upon overexpression of LRRK2 WD40 domain constructs; such output might be read as a dominant negative effect of ectopic LRRK2 WD40 executed on endogenous LRRK2 function. RACK1 is a seven-bladed WD40 propeller protein (19,40), reported to bind and anchor recycling endosomal vesicles to centrosomes (57). Accordingly, we reported that RACK1 significantly reduces SV recycling (but not spatial segregation) once it is overexpressed in neurons and that it cosediments with pure SV.…”
Section: Discussionmentioning
confidence: 84%
See 1 more Smart Citation
“…Accordingly, we observed a severe reduction in the transport of synaptotagmin-labeled (cycling) SV to distal parts of neuronal processes upon overexpression of LRRK2 WD40 domain constructs; such output might be read as a dominant negative effect of ectopic LRRK2 WD40 executed on endogenous LRRK2 function. RACK1 is a seven-bladed WD40 propeller protein (19,40), reported to bind and anchor recycling endosomal vesicles to centrosomes (57). Accordingly, we reported that RACK1 significantly reduces SV recycling (but not spatial segregation) once it is overexpressed in neurons and that it cosediments with pure SV.…”
Section: Discussionmentioning
confidence: 84%
“…The LRRK2 WD40 G2385R variant as well as FLAG-and RFP-tagged LRRK2 consisting of residues 1 to 2141 (hereinafter termed LRRK2 1-2141) were generated by site-directed mutagenesis using a QuikChange mutagenesis kit (Stratagene). Cloning of pGEX-RACK1 and full-length FLAG-LRRK2 was described previously (18)(19)(20). LRRK2 WD40 consisting of aa 2148 to 2527 with six copies of a His tag (6ϫHis) was cloned into pETM11.…”
Section: Cells/mmmentioning
confidence: 99%
“…These include various cancers [27,51,52,53,54,55,56,57,58,59], liver fibrogenesis [60], cardiac hypertrophy [61], and asthma [62]. There is also evidence to suggest that increases in ADAM12 are associated with adverse outcomes in pregnancy [63,64,65], and that it may also be used as a first [66] or second [67,68] trimester screen for Down syndrome, although these data are considerably more debated.…”
Section: : Adam12mentioning
confidence: 99%
“…Bourd-Boittin et al ., have demonstrated that ADAM12 is a binding partner for the receptor for activated protein kinase C (RACK1), a homolog of the β-subunit of heterotrimeric G proteins [60]. Both RACK1 and ADAM12 are overexpressed in patients with hepatic carcinomas.…”
Section: : Adam12mentioning
confidence: 99%
See 1 more Smart Citation